ANALISIS PENGENDALIAN INTERNAL DALAM AKTIVITAS PEMBERIAN KREDIT DENGAN PENERAPAN KEARIFAN LOKAL “PADE GELAHANG” PADA SEKAA TUAK “ADA TUARA” DESA SEMBIRAN - I Kadek Ari Mahardika; Made Aristia Prayudi (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
The present research aimed to find out how the application of local wisdom “Pade Gelahang” as an internal control system in giving credit to SekaaTuak “Ada Tuara”. This study used qualitative research. The data used in this research were primary data and secondary data. The result of this study showed that; the internal control system in Sekaa Tuak “Ada Tuara” based on the awig-awig Sekaa Tuak along with applying local wisdom “Pade Gelahang”. The “ketekel” sanction was the application of the local wisdom “Pade Gelahang” which namely the imposition of a 50% fine of the interest for sekaa tuak members not pay credit. The application of local wisdom "Pade Gelahang” was also in the form of no collateral required in making loans. Local wisdom “Pade Gelahang” as the internal control system in the lending activity at the Sekaa Tuak “Ada Tuara” was so effective in decreasing the bad loans occurrence.